PENGARUH PEMBERIAN ELISITOR JAMUR Phytium aphanidermatum (Edson) Fitzp. TERHADAP KANDUNGAN AJMALISIN PADA KULTUR KALUS BERAKAR Catharanthus roseus (L.) G. Don - Aprianita, Aprianita; RR, Esyanti; Siregar, AH (Research Center for Biology-Indonesian Institute of Sciences, 2003)
An experiment to study the effect of ellicitor derived from Phytium aphanidermatum On ajmalicine content of Catharanthus roseus root- callus culture has been conducted. Root-callus was induced from left segment, and grew optimally on Zenk medium with the addition of 10-7 M BAP and 10-5 M NAA. Root-callus was subcultured three times, and followed with elicitation with elicitor derived from autoclaved P. aphanidermatum. The concentration tested were 0.50, 0.5, 1.0 and 5.0 mg DW/ml, and harcested at 0,18,36 and 72 hours. The ajmalicine was analyzed qualitatively and quantitatively by using High Performance Liquid Chromatography (HPLC). The result showed that ajmalicine content was influenced significantly by concentration of ellicitor and harvesting time. A significant increase of ajamalicine content (153.29 ± 1.61 mg/g DW) was achieved by additon of 1 mg Dw/ml ellicitor after 36 hours incubation.